2005
DOI: 10.1016/j.ecresq.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of quality in preschool child care classrooms: An exploratory and confirmatory factor analysis of the early childhood environment rating scale-revised

Abstract: Abstract:The purpose of the current study was to examine the psychometric properties of the Early Childhood Environment Rating Scale-Revised (ECERS-R) with a large sample (1313 classrooms). We explored both the seven subscales and the possibility of fewer distinct aspects of quality being measured by the scale. The large sample size allowed both exploratory and confirmatory factor analyses to be performed. The results showed two distinct factors, Activities/Materials (nine items) and Language/Interaction (seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 12 publications
4
56
2
2
Order By: Relevance
“…Although this result is lower from a quantitative perspective, from a qualitative point of view it is similar to those obtained in other research studies carried out in Spain (Cryer, Tietze, Burchinal, Leal & Palacios, 1999;Lera, 2007;Tietze, Cryer Bairrao, Palacios & Wetzel, 1996;Vermeer et al, 2010). It is, however, lower than those obtained in other European (Cryer et al, 1999;Sylva et al, 2006;Tietze et al, 1996) and North American studies (Cassidy, Hestenes, Hegde, Hestenes & Mims, 2005;Cryer et al, 1999;Mashburn et al, 2008;Peisner-Feiberg et al, 2001). Thus, bearing in mind the positive influence of good childcare quality during early childhood on later longterm development (Vandell et al, 2010) and the key role played by the school in children's development (Burchinal et al, 2000, López, 2009, we would like to highlight the importance of taking steps to improve global process quality in preschools.…”
Section: Discussioncontrasting
confidence: 51%
“…Although this result is lower from a quantitative perspective, from a qualitative point of view it is similar to those obtained in other research studies carried out in Spain (Cryer, Tietze, Burchinal, Leal & Palacios, 1999;Lera, 2007;Tietze, Cryer Bairrao, Palacios & Wetzel, 1996;Vermeer et al, 2010). It is, however, lower than those obtained in other European (Cryer et al, 1999;Sylva et al, 2006;Tietze et al, 1996) and North American studies (Cassidy, Hestenes, Hegde, Hestenes & Mims, 2005;Cryer et al, 1999;Mashburn et al, 2008;Peisner-Feiberg et al, 2001). Thus, bearing in mind the positive influence of good childcare quality during early childhood on later longterm development (Vandell et al, 2010) and the key role played by the school in children's development (Burchinal et al, 2000, López, 2009, we would like to highlight the importance of taking steps to improve global process quality in preschools.…”
Section: Discussioncontrasting
confidence: 51%
“…Alguns estudos sobre as escalas já foram publ cados e têm o foco nas suas propr edades ps cométr cas (Cass dy, Hestenes, Hedge, Hestenes & M ms, 2005;Perlman, Zellman & Le, 2004;Saka , Wh tebook, W shard & Howes, 2003).…”
Section: A M Carvalho and A S Pereiraunclassified
“…Third, researchers may decide to limit the number of items to reduce the time-consuming training and administration of the full ERS. Previous analyses of US studies (e.g., Cassidy et al 2005b;Perlman et al 2004;Scarr et al 1994) have shown that a shorter version of the ECERS-R is a good proxy for scores on the full scale. The current study examines whether shortened versions of the ERS yield the same results as the full scale in a larger international sample of studies.…”
Section: Process Quality and Scale Characteristicsmentioning
confidence: 99%